Identity Integration as a Pedagogical Implication in E. R. Braithwaite’s To Sir with Love - Labh, Bhabes Kumar; Sapkota, Ram Chandra (Journal of Development Review, 2023)
Educators’ perspectives, facilitation methods, time constraints, topics of discussion as well as students’ identity vulnerability contribute to academic atmosphere inside class where educators find it challenging to foster mutual understanding and identity integration for effective teaching-learning. It can be a turbulent and emotionally stressful experience for educators to understand themselves in relation to their students. In this light, this paper, using Mark Bracher’s notion of radical pedagogy, focuses on the need to explore students’ identity in order to enhance their academic capacity and learning. Specifically, we argue that in order to meet all students’ learning needs, school educators must explore their own identity through self-analysis along with the identity vulnerabilities of students and integrate their students’ identity needs to enhance classroom dynamics as well as to maintain social justice for better pedagogical implications.